Expression Analysis of Nitrogen Metabolism-Related Genes Reveals Differences in Adaptation to Low-Nitrogen Stress between Two Different Barley Cultivars at Seedling Stage - Zhiwei Chen; Chenghong Liu; Yifei Wang; Ting He; Runhong Gao; Hongwei Xu; Guimei Guo; Yingbo Li; Longhua Zhou; Ruiju Lu; Jianhua Huang (International Journal of Genomics)
The excess use of nitrogen fertilizers causes many problems, including higher costs of crop production, lower nitrogen use efficiency, and environmental damage. Crop breeding for low-nitrogen tolerance, especially molecular breeding, has become the major route to solving these issues. Therefore, in crops such as barley (Hordeum vulgare L.), it is crucial to understand the mechanisms of low-nitrogen tolerance at the molecule level. In the present study, two barley cultivars, BI-04 (tolerant to low nitrogen) and BI-45 (sensitive to low nitrogen), were used for gene expression analysis under low-nitrogen stress, including 10 genes related to primary nitrogen metabolism. The results showed that the expressions of HvNIA2 (nitrite reductase), HvGS2 (chloroplastic glutamine synthetase), and HvGLU2 (ferredoxin-dependent glutamate synthase) were only induced in shoots of BI-04 under low-nitrogen stress, HvGLU2 was also only induced in roots of BI-04, and HvGS2 showed a rapid response to low-nitrogen stress in the roots of BI-04. The expression of HvASN1 (asparagine synthetase) was reduced in both cultivars, but it showed a lower reduction in the shoots of BI-04. In addition, gene expression and regulation differences in the shoots and roots were also compared between the barley cultivars. Taken together, the results indicated that the four above-mentioned genes might play important roles in low-nitrogen tolerance in barley.